2015
DOI: 10.1017/s0033291715000483
|View full text |Cite
|
Sign up to set email alerts
|

Expression quantitative trait loci (eQTLs) in microRNA genes are enriched for schizophrenia and bipolar disorder association signals

Abstract: Background Schizophrenia (SZ) and bipolar disorder (BD) have substantial negative impact on the quality of human life. Both, microRNA (miRNA) expression profiling in SZ and BD postmortem brains [and genome-wide association studies (GWAS)] have implicated miRNAs in disease etiology. Here, we aim to determine whether significant GWAS signals observed in the Psychiatric Genetic Consortium (PGC) are enriched for miRNAs. Method A two-stage approach was used to determine whether association signals from PGC affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 92 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Genetic variants in miRNA regulome may affect miRNA transcription and regulation of targeted genes, and finally contribute to the development of complex traits and diseases. Some GWAS‐based studies have comprehensively investigated the associations of single nucleotide polymorphisms (SNPs) in miRNA regulome with human traits and diseases . Bulik‐Sullivan et al .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic variants in miRNA regulome may affect miRNA transcription and regulation of targeted genes, and finally contribute to the development of complex traits and diseases. Some GWAS‐based studies have comprehensively investigated the associations of single nucleotide polymorphisms (SNPs) in miRNA regulome with human traits and diseases . Bulik‐Sullivan et al .…”
mentioning
confidence: 99%
“…Williamson et al . revealed that SNPs associated with miRNA expression were enriched in the significant GWAS signals of some special diseases …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…So, a statistical and computational approach correlates data from genetic patterns of all markers with the expression of all measured genes (Michaelson et al, 2009 ). With regard to schizophrenia, this approach allowed to find several new risk loci in blood samples (3p21 and 10q24 and SNPs in two calcium-channels subunits genes; Cross-Disorder Group of the Psychiatric Genomics, 2013 ) and also was recently used to evaluate the potential role of microRNA in its etiology (Williamson et al, 2015 ) or the genetic pleiotropy between immune and psychiatric disorders (Andreassen et al, 2015 ; Wang Q. et al, 2015 ).…”
Section: Quantitative Trait Loci (Qtl)mentioning
confidence: 99%